BUILDING A CULTURE OF QUALITY IN ISLAMIC EDUCATION STRATEGIES AND IMPLEMENTATION - Abdullah, Burhan; A. Latief Arung Arafah; Siti Patimah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
Islamic education has an important role in giving birth to a generation of achievers and noble characters. Efforts to achieve this goal require commitment and hard work from all parties, including building a quality culture. This article discusses the concepts, strategies and steps for implementing a culture of quality in Islamic education. Various challenges in realizing this quality culture are also studied, along with solutions and suggestions for overcoming them. It is concluded that building a culture of quality in Islamic education requires commitment, hard work and cooperation from the entire academic community as well as support from various parties. By implementing the various strategies and solutions presented in this article, it is hoped that a culture of quality can be firmly embedded in the Islamic education environment in Indonesia.